Complications of percutaneous vertebroplasty: An analysis of 1100 procedures performed in 616 patients. Issue 24 (June 2016) - Saracen, Agnieszka; Kotwica, Zbigniew
Abstract : Abstract: Percutaneous vertebroplasty (PVP) is a minimally invasive procedure widely used for the treatment of pain due to vertebral fractures of different origins—osteoporotic, traumatic, or neoplastic. PVP is minimally invasive, but the complications are not rare; however, they are in most cases not significant clinically. The most frequent is cement leakage, which can occur onto veins, paravertebral soft tissue, into the intervertebral disk, or to the spinal canal, affecting foraminal area or epidural space. We analyzed results of treatment and complications of vertebroplasty performed with the use of polimethylomethylacrylate cement (PMMA) on 1100 vertebrae, with a special regard to the severity of complication and eventual clinical manifestation. One thousand one hundred PVP were analyzed, performed in 616 patients. There were 468 (76%) women and 148 men (24%), 24 to 94-year old, mean age 68 years. From 1100 procedures, 794 treated osteporotic and 137 fractures due to malignant disease, 69 PVP were made in traumatic fractures. One hundred patients had painful vertebral hemangiomas. Seven hundred twenty-six (66%) lesions were in thoracic, and 374 (34%) in lumbar area. Results of treatment were assessed using 10 cm Visual Analogue Scale (VAS) 12 hours after surgery, 7 days, 30 days, and then each 6 months, up to 3 years. Before surgery all patients had significant pain 7 to 10 in VAS scale, mean 8.9 cm. Twelve  hours after surgery 602 (97.7%) reported significant relief of pain, with mean VAS of 2, 3 cm. Local complications occurred in 50% of osteoporotic, 34% of neoplastic, 16% of traumatic fractures, and 2% of vertebral hemangiomas. The most common was PMMA leakage into surrounding tissues—20%; paravertebral vein embolism—13%; intradiscal leakage—8%; and PMMA leakage into the spinal canal—0.8%. Results of treatment did not differ between patients with and without any complications. From 104 patients who had chest X-ray or CT study performed after surgery, pulmonary embolism was noted in 2 patients, but without any clinical symptoms. Only 1 patient—with PMMA leakage into the spinal canal required surgical decompression In conclusion, PVP is effective in decreasing the level of pain in compression vertebral fractures. Complications occur in almost half of the patients but in more than 95% of them do not produce any clinical symptoms.